Meninggalkan Ayah dan Ibu: Studi Komparatif Matius 19:5-6 dengan Tradisi Menjae pada Keluarga Suku Pakpak - Julkipri Manik; Reymond Sianturi; Bernhardt Siburian; Megawati Manullang; Nurelni Limbong (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This study aims to compare the concept of leaving father and mother in Matthew 19:5-6 with the practice of Menjae in Pakpak Tribal Culture. In addition, this study will also analyze the meaning of leaving father and mother in Matthew 19:5-6 and explore the meaning of Menjae in the Pakpak Family Cultural Tradition. Through this research, it will see the parallels between leaving father and mother in Matthew 19:5-6 and Menjae in the Pakpak Family Cultural Tradition. The author also wants to mean whether culture and the Bible sometimes disagree or become harmonized and see the positive value of the implementation of Menjae Culture in Pakpak family traditions.